Some tests on the measurement of the modulation transfer function technique of screen-film system - Wan Hassan, Wan Muhamad Saridan (Penerbit UTM Press, 1999)
A method to determine the modulation transfer function (MTF) of screen-film system was tested by measuring the MTF of a mammography and a conventional radiography systems. The method was further tested by measuring MTF obtained from x-rays exiting from two tissues equivalent phantoms. The MTF of the mammography system was higher than that of conventional radiography system confirming general correctness of the method. The MTFs obtained from the two equivalent phantoms agreed very well which indicate that the equivalent could be shown by the method. The study gives the experimental proof for the appropriateness of the method.